2006
DOI: 10.1176/appi.ps.57.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Innovations: Rehab Rounds: Problem-Solving Skills for Cognitive Rehabilitation Among Persons With Chronic Psychotic Disorders in Italy

Abstract: Studies have shown that teaching persons with mental illness to identify and cope with their real-life problems yields substantial clinical improvements. In Italy a structured problem-solving group was established in a day treatment center in 2003. This column describes the approach and focuses on the outcomes achieved by 15 patients with severe mental illness who were in this group. After completion of the problem-solving program, significant improvements were noted in symptom scores on the Positive and Negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…We followed Fallon unpublished manual [ 23 ] very similar to that of Barbieri, et al [ 24 ]. A structured method of resolving problems, such as PST, allows patients with schizophrenia to develop solutions to everyday problems, by assigning them a role of responsibility and allowing individuals to experience an active management of the problems themselves.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed Fallon unpublished manual [ 23 ] very similar to that of Barbieri, et al [ 24 ]. A structured method of resolving problems, such as PST, allows patients with schizophrenia to develop solutions to everyday problems, by assigning them a role of responsibility and allowing individuals to experience an active management of the problems themselves.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…For the PST , we followed the Falloon approach [ 23 ] better decribed in an unpublished manual that is quite similar of that edited by Barbieri et al [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improvements in verbal memory and executive functions with median to large effect sizes have been observed in cognitive remediation approaches for adolescent psychosis together with improvements in daily living, adaptive functioning, and family burden [57]. Furthermore, particular improvements in verbal fluency measures, together with significant positive and negative symptom reductions, have also been observed in specifically targeted problem-solving program interventions [58]. Verbal fluency performance has shown to be one of the most impaired cognitive functions in first-episode schizophrenia patients and individuals at ultra-high-risk for psychosis (i.e., specifically semantic verbal fluency [59] and one of the best cognitive predictors for psychosocial functioning [60]).…”
Section: Discussionmentioning
confidence: 99%
“…The fourth study was conducted in day treatment centres and showed significant clinical and neurocognitive benefits after 6 months (Table II). These were also significantly greater than those assessed in a cohort participating in manual activities of over a similar period (Barbieri et al, 2006). All four Italian centres have used the same manual for the problem solving training (Falloon, 2000b) and have expressed interest in controlled trials of the methods.…”
Section: Pilot Studiesmentioning
confidence: 93%
“…It is divided into 4 phases dealing with the real life problems of the group members of increasing cognitive complexity and emotional distress (Barbieri et al, 2006). An initial orientation includes education about schizophrenia and its treatment, development of relapse prevention plans to detect and respond to early signs of exacerbation, clarifying specific personal life goals and defining a list of problems that represent the major obstacles to overcome in the achievement of those goals.…”
Section: A Comprehensive Problem Solving Training Course For People Wmentioning
confidence: 99%